Visual Application in Multi-touch Tabletop for Mathematics Learning: A Preliminary Study - Tyng, Khoo Shiang; Zaman, Halimah Badioze; Ahmad, Azlina (Visual Informatics: Sustaining Research and Innovations, 2011)
Multi-touch technology on tabletop appears as a promising tool in collaborative learning with or without the presence of a teacher. It can overcome some of the problems faced in using desktop computer in education since it allows single user. This paper presents a preliminary study conducted for a research project in developing a visual application in multi-touch tabletop for preschool Mathematics called MEL-Vis. The study was conducted on eight preschool’s teachers and nine primary school teachers. The results of the preliminary study showed that the topics of addition and subtraction operations were the major problems in learning and teaching of Mathematics in the preschool and at Elementary Level (Primary One). Students were found to have difficulty in understanding the concepts of addition and subtraction operations.